2017
DOI: 10.5935/2359-4802.20170004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of Doxorubicin Treatment and Physical Activity: A Systematic Review

Abstract: The present study investigated whether the practice of exercise has a protective effect against cardiac toxicity induced by doxorubicin (DOX). A systematic review of randomized clinical trials evaluating the role of exercise in the control or prevention of DOX-induced cardiotoxicity was performed in MEDLINE and LILACS databases. Studies that did not address the main subject of this review, did not mention physical exercise or DOX, studies that evaluated other types of anthracycline-induced toxicities only (mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
7
0
11
Order By: Relevance
“…In parallel with the increase in the number of confirmed cases of cancer, new modalities of treatment have increased cancer survival and possibilities of cure. However, the treatment may cause several adverse effects including treatment-related cardiotoxicity that may lead to poorer prognosis than cancer itself, and also affect treatment continuation [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the increase in the number of confirmed cases of cancer, new modalities of treatment have increased cancer survival and possibilities of cure. However, the treatment may cause several adverse effects including treatment-related cardiotoxicity that may lead to poorer prognosis than cancer itself, and also affect treatment continuation [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiotoxicity studies showed that EO supplementation was able to prevent changes caused by doxorubicin, commonly used in chemotherapy [ 94 ]. The added EO diet improved fractional shortening of the left ventricle and increased the levels of enzymes associated with cardiac metabolism, such as β-hydroxyacyl-CoA dehydrogenase, phosphofructokinase, citrate synthase, complex II enzyme activities, and ATP synthase.…”
Section: Biological Eo Activities: Application In the Prevention Amentioning
confidence: 99%
“…42,43 No entanto, os mecanismos desse efeito ainda não foram completamente elucidados. 44,45 Em uma revisão sobre os efeitos de exercício físico na resposta cardiovascular de pacientes com câncer de mama, Sturgeon et al 46 revelaram uma falta de estudos focados em cardiotoxicidade em humanos. Eles apontaram que, apesar de poucos estudos pré-clínicos indicarem uma diminuição na frequência cardíaca em repouso e na pressão arterial em pacientes que praticam exercício aeróbio durante e após a quimioterapia, esses parâmetros não são suficientes para indicar boa função cardíaca.…”
Section: Tabela 2 -Resumo Dos Estudos Selecionados Para a Variável Prunclassified